Deep brain stimulation in the caudal zona incerta versus best medical treatment in patients with Parkinson's disease: a randomised blinded evaluation. Issue 7 (31st January 2018) - Blomstedt, Patric; Stenmark Persson, Rasmus; Hariz, Gun-Marie; Linder, Jan; Fredricks, Anna; Häggström, Björn; Philipsson, Johanna; Forsgren, Lars; Hariz, Marwan
Abstract : Background: Several open-label studies have shown good effect of deep brain stimulation (DBS) in the caudal zona incerta (cZi) on tremor, including parkinsonian tremor, and in some cases also a benefit on akinesia and axial symptoms. The aim of this study was to evaluate objectively the effect of cZi DBS in patients with Parkinson's disease (PD). Method: 25 patients with PD were randomised to either cZi DBS or best medical treatment. The primary outcomes were differences between the groups in the motor scores of the Unified Parkinson's Disease Rating Scale (UPDRS-III) rated single-blindly at 6 months and differences in the Parkinson's Disease Questionnaire 39 items (PDQ-39). 19 patients, 10 in the medical arm and 9 in the DBS arm, fulfilled the study. Results: The DBS group had 41% better UPDRS-III scores off-medication on-stimulation compared with baseline, whereas the scores of the non-surgical patients off-medication were unchanged. In the on-medication condition, there were no differences between the groups, neither at baseline nor at 6 months. Subitems of the UPDRS-III showed a robust effect of cZi DBS on tremor. The PDQ-39 domains 'stigma' and 'ADL' improved only in the DBS group. The PDQ-39 summary index improved in both groups. Conclusion: This is the first randomised blinded evaluation of cZi DBS showing its efficacy on PD symptoms. The most striking effect was on tremor; however, the doses of dopaminergic medications could not be decreased. cZi DBS in PD may be an addition to existing established targets, enabling tailoring the surgery to the needs of the individual patient.